2021
DOI: 10.1111/ejh.13649
|View full text |Cite
|
Sign up to set email alerts
|

Intensive induction regimens after deferring initial therapy for mantle cell lymphoma are not associated with improved survival

Abstract: Introduction While most patients with mantle cell lymphoma (MCL) receive therapy shortly after diagnosis, a subset of patients with indolent‐behaving disease can safely defer treatment. In this subgroup, we evaluated the importance of treatment intensity in patients with MCL who defer initial therapy. Methods Out of 1134 patients with MCL from 12 academic centers, we analyzed 219 patients who initiated therapy at least 90 days after diagnosis. Patients who received induction with high‐dose cytarabine and/or au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The details of the cohort are described elsewhere. 10 , 11 The study was institutional review board approved at all the participating sites and was conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the cohort are described elsewhere. 10 , 11 The study was institutional review board approved at all the participating sites and was conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…[70]. Similarly, Shanmugasundaram et al showed that those who deferred therapy had a superior 5-year OS of 83.6% versus 72.6% compared to those treated immediately at diagnosis (p = 0.03) [71].…”
Section: Indolent MCLmentioning
confidence: 96%
“…Subsequent studies have also reported favorable outcomes in patients able to undergo initial observation [ 12 , 70 , 71 , 72 ]. Martin et al showed that delayed treatment (defined as greater than three months) before initiation of first-line therapy was associated with improved OS, compared to those who started treatment immediately.…”
Section: Prognostic Factors Determined Following Treatmentmentioning
confidence: 99%
See 1 more Smart Citation